2021
DOI: 10.3389/fmolb.2021.814318
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomic Profiling Reveals the Reducing Lipid Accumulation Effect of Dietary Taurine in Groupers (Epinephelus coioides)

Abstract: A lipidomic analysis was conducted to provide the first detailed overview of lipid molecule profiles in response to dietary lipid and taurine and associations of liver lipid-lowering effects of dietary taurine with lipid molecular species and the positional distributions of fatty acids in the liver of juvenile orange-spotted groupers (Epinephelus coioides). The results indicated that the liver was more sensitive to varied dietary lipid and taurine contents than the muscle with regard to lipid molecules. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…However, the underlying mechanism involved in the regulation of lipid metabolism still remains unclear. Recent studies have shown that dietary taurine supplementation in 15% fat feed could reduce lipid accumulation through reducing the contents of triglyceride molecules containing 18:2n–6 at the sn – 2 and sn – 3 positions [ 25 ] and through accelerating lipid absorption of taurine−conjugated bile acids and fatty acid β-oxidation, and inhibiting lipogenesis [ 26 ]. However, determining how dietary taurine modulates lipid metabolism of fish at the transcriptional level has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…However, the underlying mechanism involved in the regulation of lipid metabolism still remains unclear. Recent studies have shown that dietary taurine supplementation in 15% fat feed could reduce lipid accumulation through reducing the contents of triglyceride molecules containing 18:2n–6 at the sn – 2 and sn – 3 positions [ 25 ] and through accelerating lipid absorption of taurine−conjugated bile acids and fatty acid β-oxidation, and inhibiting lipogenesis [ 26 ]. However, determining how dietary taurine modulates lipid metabolism of fish at the transcriptional level has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Other fish species displayed a comparable result, although the occurrence rate of these findings varied. In Nile tilapia ( Oreochromis niloticus ) and orange-spotted grouper ( Epinephelus coioides ) muscular tissues, TG emerged as the dominant lipid class, with PC and PE following closely behind [ 23 , 24 ]. Given that TG primarily functions as a source of energy [ 25 ], PC and PE play crucial roles in the proper integration of membrane proteins and membrane fusion and fission processes [ 24 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…MUFA, especially 18 : 1n−9, is a "healthy" fatty acid for human body, which can remove bad cholesterol and protect cardiovascular and cerebrovascular health, etc. [42]. The concentrations of MUFA were 361.46 μg/g, dominated by 18 : 1n−9c (146.34 μg/g).…”
Section: The Fatty Acids Profiles In Musclementioning
confidence: 93%